Effect of Nitrogen Fertigation by Sprinkler Irrigation on Sugar Beet Crop Performance - Nouri, Hamidah (2009)
It is crucial to make field management strategy by understanding of spatial and temporal variability of effective elements such as soil, water and plant properties. The impact of nitrogen fertigation by sprinkler irrigation would be a valuable step in support of environmental preservation and natural resources conservation. This research has focused on the spatial and temporal distribution of N fertigation by sprinkler irrigation and its effect on soil and plant properties to determine the relationship among fertigation distribution pattern and crop performance. The field variability study was carried out in the Fesaran village in east part of Esfahan city in Esfahan Province, Iran. Geostatistical sampling method was selected for an accurate interpolation by kriging to produce spatial and temporal variability maps. A total of 162 soil samples and 81 plant samples were collected and locations recorded using Differential Global Positioning System (DGPS). To describe the variability of soil and plant status, soil and plant nutrient response to the nitrogen fertilizer application by sprinklers was studied by analyzing 7 soil elements including N, P, K, CEC, OM, EC, and PH under two conditions, pre-treatment (before fertigation) and posttreatment (after fertigation). The sugar beet crop performance was based on 6 crop properties that include leaf N content, tuber moisture content, tuber sugar content, tuber weight, number of tubers in each square meter and yield. Variability maps were obtained using Geographical Information System (GIS) and Geostatistical statistics (GS+) software. Statistical analysis, geostatistical analysis and spatial analysis were employed to analyze the data. Data statistical analysis consist of descriptive analysis, T-Test (Pairwise two-tail), correlation (Pearson two-tail) and ANOVA (Duncan and SNK) and regression were derived from Statistical Package for the Social Sciences (SPSS) and Statistical Analysis System (SAS) software. The impact of N fertigation through sprinkler irrigation on spatial and temporal pattern of soil properties and spatial variability of sugar beet crop performance was studied through statistical analysis and visualization of spatial variability maps. The results show that the highest variability in available P (CV =89.7 %) and K (CV =53.26 %) between selected soil properties. It could be related to non-uniform fertilization of potash and phosphate pre-plant that were applied manually. The least variability was seen in soil pH (CV =0.97 %) and soil OM (CV =3.04 %).That is an evidence of very low variability of soil pH and OM through and across the study area. Low variability of soil N (CV =12.44 %, CV =14.7 %) would be a key point to encourage farmers to replace fertigation by sprinkler irrigation instead of current methods.The highest variability of crop properties belonged to tuber weight (CV=44.8 %) while the least variability was in tuber moisture content (CV=6.04 %) and tuber sugar content (CV=6.38 %) which points out the low variability of sugar and moisture content of tubers. Crop properties such as yield, tuber sugar content, tuber numbers, tuber moisture content and N leaf content have low variability (CV ≤ 25 %), except tuber weight with moderate variability. Spatial variability map displays concentration of the higher yield was seen in central area compared to least yield in the north west of the study area. Fewer tubers in the north and east of the study area compared to more tubers in the south and west. Interestingly, for those areas which have heavier tubers, the map shows fewer numbers of tubers. Plant performance analysis shows a negative significant correlation of leaf N content with sugar content of tuber at 95 % confidence. Tuber weight has a negative correlation to the number of tubers but positive correlation to the tuber moisture content. It indicates the higher moisture content causes heavier tuber but the grid which has more number of tubers has the lighter tubers. There is a negative correlation of tuber weight and number of tubers but positive significant correlation of number of tubers and sugar content. It indicates that more tubers with lighter weight have higher sugar content. Surprising result shows the negative correlation of leaf N content and sugar content.